(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Vocabulary knowledge is a fundamental component of second language acquisition, serving as the basis for effective communication, comprehension, and academic performance. While grammar provides structural support, vocabulary conveys meaning and enables learners to understand texts and interact fluently. This expanded article examines a wide range of strategies used for English vocabulary learning, including cognitive, metacognitive, social, and affective approaches, as well as techniques enhanced by modern technology. Drawing on research in applied linguistics, psychology, and pedagogy, the article highlights best practices for vocabulary instruction and learner autonomy. Recommendations for educators and learners conclude the discussion.